Potential Therapeutic Applications of Synthetic Conotoxin s-cal14.2b, Derived from Californiconus californicus, for Treating Type 2 Diabetes - Pavel H. Lugo-Fabres; Leslie M. Otero-Sastre; Johanna Bernáldez-Sarabia; Tanya A. Camacho-Villegas; Noemi Sánchez-Campos; Janeth Serrano-Bello; Luis A. Medina; Saé Muñiz-Hernández; Lizbeth de la Cruz; Isabel Arenas; Antonio Barajas-Martínez; David E. Garcia; et al. (Biomedicines, 2021)
The FDA’s approval of peptide drugs such as Ziconotide or Exendin for pain relief and diabetes treatment, respectively, enhanced the interest to explore novel conotoxins from Conus species venom. In general, conotoxins can be used in pathologies where voltage-gated channels, membrane receptors, or ligands alter normal physiological functions, as in metabolic diseases such as Type 2 diabetes. In this study, the synthetic cal14.2b (s-cal14.2b) from the unusual Californiconus californicus demonstrated bioactivity on NIT-1 insulinoma cell lines stimulating insulin secretion detecting by high performance liquid chromatography (HPLC). Accordingly, s-cal14.2b increased the CaV1.2/1.3 channel-current by 35 ± 4% with a recovery τ of 10.3 ± 4 s in primary cell culture of rat pancreatic β-cells. The in vivo results indicated a similar effect of insulin secretion on mice in the glucose tolerance curve model by reducing the glucose from 500 mg/dL to 106 mg/dL in 60 min, compared to the negative control of 325 mg/dL at the same time. The PET-SCAN with radiolabeling 99mTc-s-cal14.2b demonstrated biodistribution and accumulation in rat pancreas with complete depuration in 24 h. These findings show the potential therapeutic use of s-cal14.2b in endocrinal pathologies such as early stages of Type 2 Diabetes where the pancreas’s capability to produce insulin is still effective.